Inter and Intra Selection Efficiency of Cotton Families (Gossypium hirsutum L.) (International Journal of Environmental Sciences, 2025)
Offspring families (F3 and F4) derived from superior crosses were grown at an agricultural farm in Baghdad Governorate\ Iraq (33.05N latitude, 44.32E longitude) for two successive years (2021-2022) by using a Randomized Completely Block Design with three replications to investigate responses for selection for seed cotton yield and its components traits. Results showed: Some lines outperformed their parents in yield and its components in both the third and fourth generations. The combinations 2-2, 3-1, and 3-4 demonstrated the best performance and stability in the yield of cotton bolls (135.06 and 145.72), (130.46 and 141.33), and (143.97 and 137.77) for the third and fourth generations, respectively. They also excelled in yield traits compared to other genetic combinations. The coefficients of inbreeding were negative for the number of fruit branches, the number of bolls per plant, and the yield of cotton bolls per plant (-9.33, -21.01, and -14.62, respectively). Genetic divergence indicated that the most distinct genetic combination was line 4-1, which formed a unique group, followed by line 9-2, which included other subgroups. However, group seven, comprising combinations 1-2 and 3-4, stood out with the best performance and highest yield of cotton bolls (139.46 grams per plant), followed by group six, which included combination 3-3 (143.97 grams per plant), and group four, which included combination 2-1 (135.06 grams per plant). These groups can be considered sources for improving the yield traits and their components of cotton bolls. Therefore, it can be concluded that the best performing and productive line was combination 3-4, which was distinguished by a unique group with combination 1-2, making it a promising candidate for selected cotton families.